Environmental Impact on Class C Quarry Mining Activities - Maisa Maisa; Nunun Nurhajati; Retno Sari Dewi; Nurani Nurani (Universitas Muhammadiyah Palu, 2023)
One of the industries that can bring in a lot of foreign exchange is mining. In this case it is recognized that the mining sector can contribute significantly to local revenue, but it should be noted that there will also be environmental and social impacts. mining activities of class C excavation materials starting from the exploration stage to exploitation and utilization have an impact on society both negatively and positively.In this study using normative research methods. The focus of this research is the impact of C excavation mining activities on the environment. Some common environmental impacts associated with quarry mining include: Habitat destruction, water pollution, air pollution, climate change and social impacts.